Seed germination demonstrates inter-annual variations in alkaline tolerance: a case study in perennial Leymus chinensis - Zhao, Dandan; Ma, Hongyuan; Li, Shaoyang; Qi, Wenwen (BMC plant biology, 2024)
The escalating issue of soil saline-alkalization poses a growing global challenge. Leymus chinensis is a perennial grass species commonly used in the establishment and renewal of artificial grasslands that is relatively tolerant of saline, alkaline, and drought conditions. Nonetheless, reduced seed setting rates limit its propagation, especially on alkali-degraded grassland. Inter-annual variations have an important effect on seed yield and germination under abiotic stress, and we therefore examined the effect of planting year on seed yield components of L. chinensis. We grew transplanted L. chinensis seedlings in pots for two (Y ), three (Y ), or four (Y ) years and collected spikes for measurement of seed yield components, including spike length, seed setting rate, grain number per spike, and thousand seed weight. We then collected seeds produced by plants from different planting years and subjected them to alkaline stress (25 mM Na CO ) for measurement of germination percentage and seedling growth. The seed setting rate of L. chinensis decreased with an increasing number of years in pot cultivation, but seed weight increased. Y plants had a higher seed setting rate and more grains per spike, whereas Y plants had a higher thousand seed weight. The effects of alkaline stress (25 mM Na CO ) on seed germination were less pronounced for the heavier seeds produced by Y plants. Na CO caused a 9.2% reduction in shoot length for seedlings derived from Y seeds but a 22.3% increase in shoot length for seedlings derived from Y seeds. Our findings demonstrate significant differences in seed yield components among three planting years of L. chinensis under pot cultivation in a finite space. Inter-annual variation in seed set may provide advantages to plants. Increased alkalinity tolerance of seed germination was observed for seeds produced in successive planting years.